Telomerase as a Target for Therapeutic Cancer Vaccines and Considerations for Optimizing Their Clinical Potential - Ellingsen, Espen Basmo; Mangsbo, Sara M.; Hovig, Eivind; Gaudernack, Gustav (Frontiers in Immunology, 2021)
Telomerase-based therapeutic cancer vaccines (TCVs) have been under clinical investigation for the past two decades. Despite past failures, TCVs have gained renewed enthusiasm for their potential to improve the efficacy of checkpoint inhibition. Telomerase stands as an attractive target for TCVs due to its almost universal presence in cancer and its essential function promoting tumor growth. Herein, we review tumor telomerase biology that may affect the efficacy of therapeutic vaccination and provide insights on optimal vaccine design and treatment combinations. Tumor types possessing mechanisms of increased telomerase expression combined with an immune permissive tumor microenvironment are expected to increase the therapeutic potential of telomerase-targeting cancer vaccines. Regardless, rational treatment combinations, such as checkpoint inhibitors, are likely necessary to bring out the true clinical potential of TCVs.